Verruciform Xanthoma in the Marginal Gingiva: A Clinical Case Report - Prachi Khuntia1 , Rashmita Nayak2 , Neeta Mohanty3 , Anurag Satpathy2 , Abhaya Chandra Das4 , Saurav (Institute of Medico-legal Publications Pvt Ltd, 2020)
Verruciform xanthoma can be described as a rare, benign lesion. It can be classified as a papillary,asymptomatic or sessile. it can be well-demarcated from the adjacent tissue and can be seen frequentlyin the alveolar mucosa and gingiva. The salient histopathological feature is the abundance of foam cells(xanthoma cells) along with macrophages present in the soft papillary tissue.1 The exact etiopathogenesisis still unknown, but the causative agents can be local factors like viral infections or trauma that have beensuggested by hypothesis. Therefore this case report aims to present a case of verruciform xanthoma locatedin the marginal gingiva (lingual aspect) and describe the clinical features and histopathological aspects.